Agreement between physical examination and dynamic sonography in infants with developmental dysplasia of the hip - Ahmet Imerci; Mihir Thacker; Richard Bowen (Acta Orthopaedica et Traumatologica Turcica, 2025)
Objective: For years, physical examination (PE) findings (e.g., Barlow, Ortolani tests, and abduction limitation) have been used as the primary screening method in the early diagnosis of developmental dysplasia of the hip (DDH). There are a limited number of studies in the literature that evaluate the agreement of PE findings and dynamic sonographic evaluation. Our aim was to evaluate the correlation between dynamic sonographic hip types and physical examination findings in infants with DDH.